2006
DOI: 10.1088/1009-0630/8/5/07
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Bipyridyl Ruthenium Dye and Its Application in Dye-Sensitized Solar Cells

Abstract: Bipyridyl ruthenium dye N3 and N719 was synthesized, purified by the gel chromatogram method and characterized by the proton NMR and UV-Vis spectra. After the purification most of the impurities that decreased the photoelectrochemical properties were removed and the open-circuit voltage (Voc), short-circuit photocurrent density ( J s c ) and overall photo-electric conversion efficiency (v) of the dye-sensitized solar cells (DSCs) increased dramatically. The standard curve of absorbance vs. concentration of N3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The solution concentration of N3 in ethanol was verified with UV−visible (UV−vis) spectroscopy (Varian Cary 300), using λ max = 538 nm and ε = 1.47 × 10 4 M −1 cm −1 . 23 Sensors were used for multiple runs, with dye removed by exposure to 2 vol % Hellmanex III solution for 24 h before cleaning as previously described above. The sensors showed no deterioration or increased noise during successive trials.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution concentration of N3 in ethanol was verified with UV−visible (UV−vis) spectroscopy (Varian Cary 300), using λ max = 538 nm and ε = 1.47 × 10 4 M −1 cm −1 . 23 Sensors were used for multiple runs, with dye removed by exposure to 2 vol % Hellmanex III solution for 24 h before cleaning as previously described above. The sensors showed no deterioration or increased noise during successive trials.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Data were acquired using QSoft (Q-Sense), processed using QTools (Q-Sense), and analyzed using Matlab (Mathworks, Inc). The solution concentration of N3 in ethanol was verified with UV–visible (UV–vis) spectroscopy (Varian Cary 300), using λ max = 538 nm and ε = 1.47 × 10 4 M –1 cm –1 . Sensors were used for multiple runs, with dye removed by exposure to 2 vol % Hellmanex III solution for 24 h before cleaning as previously described above.…”
Section: Methodsmentioning
confidence: 99%
“…13 Finally, it has been reported that the purity of N3 and N719 has a profound inuence on their performance as sensitizers in DSC devices. 14 This has led to the development of modied bipyridyl ligands which have been used to prepare sensitizers which do not require such extensive purication during the dye synthesis. 15 Whilst the aforementioned modications of the organic ligands enable the properties of Ru dyes to be tuned, these dyes are still an expensive component of DSC devices because ruthenium is an expensive raw material, the synthetic procedures are multi-step and dye purication is complicated.…”
mentioning
confidence: 99%
“…This is an important aspect when engineering these materials for DSSCs as the dye absorbs green light more strongly than red and as a result, the DSSC performs better under green illumination. 43,23 Since the red and green upconversion processes compete for upconverted energy, it is important to ensure that the amount of a-phase is minimized in order to maximize the coupling of the upconverted light to the solar cell through green upconversion. The upconversion uorescence spectra of the as-prepared UC sub-microcrystals and the composite UC materials are shown in Fig.…”
Section: Upconversion Compositesmentioning
confidence: 99%